The Belgian industrial confidence indicator: leading indicator of economic activity in the euro area? - Jean-Jacques Vanhaelen; Luc Dresse; Jan De Mulder (National Bank of Belgium, 2000)
The international press has recently reported on the widely-held view in the financial markets that the movement of the Belgian industrial confidence indicator might precede the euro area business cycles. The initial purpose of this paper is to assess whether this market perception is more than a simple optical illusion, resulting from the inspection of graphical representations of the data. For that, explicitly formalised methods are used to identify the timing of turning points in the industrial confidence indicators for Belgium and for the euro area, and the statistical significance of the differences in timing has been assessed using the Randomization Test proposed by Banerji. We conclude that the turning points in Belgium do in fact significantly lead turning points in the euro area from 1993 onwards. The leading nature of the Belgian industrial confidence indicator is not really surprising, as changes in the business cycle stages in Belgium seem to have been ahead of changes in the euro area during the period from 1985 to the first quarter of 2000. Among the three different reference series used to compare the business cycle movements in Belgium and in the euro area, the null hypothesis that turning points in Belgium do not lead those in the euro area is rejected at a confidence level above 90 p.c. in the case of GDP and of the degree of utilisation of production capacity in manufacturing industry. The leading nature is more pronounced for the sub-period beginning with the first quarter of 1993, especially in the case of GDP. However, the comparison of the movements of the industrial production indices does not confirm these conclusions. Due to the lack of sufficiently long time series for the euro area it was not possible to check whether differences in the economic structure could explain the leading nature of the activity in Belgium. However, using partial industrial confidence indicators, three factors (specialisation in intermediate goods, openness and high representation of small and medium-sized enterprises) that might explain why the Belgian business indicator and Belgian activity seem to lead their euro area counterparts were investigated, but could not be validated by the data. As it seems to be impossible to identify one or more sectors or groups of enterprises accounting for the leading nature of Belgian economic activity when looking at turning points, at least when using the business survey data, it looks as if this leading nature is a kind of general feature of the Belgian economy.
Keywords: 330; Wirtschaftsindikator; Frühindikator; Belgien; EU-Staaten